Investigating the ways in which virtual environments could influence aircraft passengers' comfort and experiences - Lewis, Laura (2015)
The experience of comfort is an important factor in passengers’ acceptance of transport systems. Comfortable cabin environments can be used as a means to differentiate between aircraft manufacturers and airlines and therefore, may be a key marketing feature. In 2010 and 2011, the European Commission presented its vision for aviation in the year 2050, highlighting the importance of enhancing passengers’ experiences. They also envisaged the use of virtual reality (VR) to provide aircraft passengers with entertainment and a means of ‘escaping from the fast pace of society’. The VR-HYPERSPACE project addressed this vision by examining the use of virtual and mixed reality technologies to enhance passenger comfort on aircraft in the year 2050. This approach to increasing comfort would be comparatively cheaper than changing the physical parameters of an aircraft.